Synthesis of Zn/SBA-15 from Rice Husk Ash Using Sonochemical Methods as a Quercetin Drug Delivery Matrix - Nur Azizah, Yulyani; Haddiana; Rudiana, Tarso (Science and Technology Indonesia, 2024)
Quercetin is a drug candidate with bioavailability but currently limited, necessitating the use of a delivery matrix, such as Santa Barbara Amorphous-15 (SBA-15). Rice husk ash, containing a significant amount of silica, served as a precursor in the synthesis of SBA-15, which can be functionalized with nanoparticles, including zinc, using sonochemical methods. Therefore, this study aimed to synthesize Zn/SBA-15 using sonochemistry and evaluate the potential as a drug delivery matrix for quercetin. SBA-15 was formed by sonication of a sodium silicate from rice husk and pore director Pluronic P-123, followed by impregnating Zn at 2%, 4%, and 6% w/w. The characterization of X-ray diffraction (XRD) and fluorescence (XRF) showed a broad peak at 2theta 18-30◦ with Zn levels of 1.89%, 3.69%, and 5.06%. Furthermore, the analysis of transmission electron microscopy (TEM) showed the presence of Zn nanoparticles with a range size of 4-14 nm. In vitro drug delivery experiments were carried out using Zn/SBA-15 at concentrations of 1:1 and 1:2 to quercetin. The in vitro test results for a drug loading of quercetin with Zn/SBA-15 6% 1:1 was 28.30 mg/g. The encapsulation efficiency was 10.96% and the drug release reached 33.64% after 240 minutes.